"Only the Wall Put a Stop to the Inflow of Monsters": Bodies and Borders in Post-Wall Berlin - Katharina Gerstenberger (Studies in 20th & 21st Century Literature, 2004)
In his seminal study Flesh and Stone, Richard Sennett showed that urban space is significantly shaped through the ways in which humans perceive their bodies…
Keywords: Flesh and Stone; Richard Sennett; urban space; urbane; body; bodies; border; borders; self-perception